Agroeconomic viability of grape-common bean intercropping - Rassele, Ronaldo Luiz; de Paiva Freitas, Silvério; Nacir Colombo, João; Krause, Marcelo Rodrigo; Barth, Heitor; Barth, Henrique Teodoro (Comunicata Scientiae, 2020)
The intercropping of agricultural crops aims to increase the profitability and the sustainability of the production systems. The objective of this study was to evaluate the agroeconomic viability of the intercropping of grape with common bean grown at different planting densities and weed management. The experimental design adopted was randomized blocks in a split-plot scheme. Treatments in the plots consisted of weed managements, mowing and chemical, and, in the subplot, the intercropping of grape with 0, 4, 8 and 12 common bean plants/linear meter. Grape-common bean intercropping and weed management did not influence the performance of grape crop. Regarding the agronomic characteristics of common bean, the highest values of plant height and yield were found with 8 and 12 plants/linear meter. Plant dry mass was higher when the common bean was intercropped with 4 plants, compared to 12 plants. For the agroeconomic indicators, land use efficiency index, monetary advantage and corrected monetary advantage, the best results were found with the intercropping with 8 bean plants, while the best results for gross income and net income were found under intercropping with 12 plants. Chemical and mowing weed managements can be recommended for the grape-common bean intercropping because they are efficient and do not affect the performance of the intercropped crops. The intercropping of grape with common bean is feasible because the gross and net income increase up to the density of 12 plants of common bean/linear meter and the intercropping with 8 plants/linear meter resulted in higher values of land use efficiency and monetary advantage.